Fetal Rhesus D Genotyping and Sex Determination from Maternal Plasma of Rhesus D-Negative Antenatal Population: The Usefulness of Conventional Polymerase Chain Reaction in Resource-limited Settings - Otchere Addai-Mensah; Edward Y. Afriyie; Samuel Asamoah Sakyi; Christian Obirikorang; Max Efui Annani-Akollor; Eddie-Williams Owiredu; Francis A. Amponsah; Richard Vikpebah Duneeh; Evans Asamoah Adu (Obstetrics and Gynecology International)
Background. This prospective cohort study evaluated the usefulness of conventional PCR in genotyping fetal Rhesus D (RhD) and sex from the maternal plasma of RhD-negative (RhD−) antenatal population in resource-limited settings. Methods. Thirty apparently healthy RhD− pregnant women with RhD positive (RhD+) partners were included. Blood samples were collected from each participant (in the third trimester of pregnancy) for DNA extraction/purification and fetal RhD genotyping. Results. Out of the 30 samples, 26 (86.7%) were found to be RhD+ while 4 (13.3%) were RhD−. The RhD+ comprised 24 (80.0%) RhD+ based on exons 5, 7, and 10 combined. Exons 5 and 7 were detected in two additional samples but not exon 10. Serological phenotyping of neonatal blood confirmed 26 RhD+ and 4 RhD−. There was a perfect agreement between the fetal RhD genotype and neonatal RhD phenotyping after delivery for exons 5 and 7 (concordance = 100%, κ = 100.0%, diagnostic accuracy = 100%, p<0.0001) while exon 10 presented with an almost perfect agreement (concordance = 93.3%, κ = 76.2%, diagnostic accuracy = 93.3%, p<0.0001). Regarding the prenatal test for the SRY gene, 9 (30.0%) were predicted to be males and the remaining 21 (60.0%) were females. All the 9 and 21 anticipated males and females, respectively, were confirmed after delivery (concordance = 100%, κ = 100.0%, diagnostic accuracy = 100%). Conclusion. Our study suggests that conventional PCR using the SRY, RhD exons 5 and 7 could be useful for predicting fetal sex and RhD from maternal peripheral blood in resource-limited settings.